Studi Penciptaan Game Komputer Pembelajaran Perbendaharaan Kata Budaya - Rachman, Anung (Institut Seni Indoensia Surakarta, 2010)
Mastery of multimedia applications, content, and aesthetics is an integral Trichotomy in the design of inter-active learning games. All three must function in proportion if a developer of multimedia applications to achieve optimal results in education. In this study the learning game was created by local cultural vocabulary. The work is the result of a combination of educational content of local culture and aesthetics of multimedia.The work of